Cryostat section assay of oestrogen and progesterone receptors in meningiomas: a clinicopathological study. Issue 1 (January 1986) - Ironside, J W; Battersby, R D; Dangerfield, V J; Parsons, M A; Timperley, W R; Underwood, J C
Abstract : Oestrogen receptors and progesterone receptors were measured in the cytosols from cryostat sections of 45 meningiomas from 40 patients (12 men, 28 women) using an isoelectric focusing technique. Near fascimile adjacent sections from the same tissue blocks were stained and examined to determine the histological subtype of the neoplasms. Appreciable levels of progesterone receptor (greater than 10 fmol/mg cytosol protein) were present in 24 (53.3%) of of the neoplasms, but no clinically important oestrogen receptor was detected in any of the tumours. Competitive binding studies on control tissue confirmed the specificity of the assay procedures. No correlation was found between progesterone receptor state and the age, sex, or menopausal state of the patients, or the histological subtype and site of the neoplasms. Four of the patients studied had multiple intracranial neoplasms, which in two were of differing progesterone receptor state. The presence of specific progesterone receptor in meningioma cytosols raises the possibility of hormonal manipulation in the treatment of this group of neoplasms.